Exome sequencing identifies novel NTRK1 mutations in patients with HSAN‐IV phenotype. Issue 4 (22nd March 2017) - Altassan, Ruqaiah; Saud, Haya Al; Masoodi, Tariq Ahmad; Dosssari, Haya Al; Khalifa, Ola; Al‐Zaidan, Hamad; Sakati, Nadia; Rhabeeni, Zuhair; Al‐Hassnan, Zuhair; Binamer, Yousef; Alhashemi, Nadia; Wade, William; et al.
Abstract : Hereditary sensory autonomic neuropathy type IV (HSAN‐IV) is a rare autosomal recessive disorder that usually begins in infancy and is characterized by anhidrosis, insensitivity to noxious stimuli leading to self‐mutilating behavior, and intellectual disability. HSAN‐IV is caused by mutations in the neurotrophic tyrosine kinase receptor type 1 gene, NTRK1, encoding the high‐affinity receptor of nerve growth factor (NGF) which maps to chromosome 1q21‐q22. Patients with HSAN‐IV lack all NGF‐dependent neurons, the primary afferents and sympathetic postganglionic neurons leading to lack of pain sensation and the presence of anhidrosis, respectively. Herein, we report nine patients from nine unrelated families with HSAN‐IV due to various mutations in NTRK1, five of which are novel. These are three missense and two nonsense mutations distributed in various domains of NTRK1 involved in binding of NGF. The affected patients had variable intellectual deficits, and some had delayed diagnosis of HSAN‐IV. In addition to being the first report of HSAN‐IV from the Arabian Peninsula, this report expands the mutational spectrum of patients with NTRK1 mutations and provides further insights for molecular and clinical diagnosis.